TINGKAT KENYAMANAN TERMAL PADA TAMAN KAMBANG IWAK PALEMBANG - Anggraeni, Dhita Wahyu (Universitas Atma Jaya Yogyakarta, 2020)
Kambang Iwak Park is one of the green open space parks in the city of Palembang. The park is used for a variety of activities, as playgrounds and sports venues, recreation areas, transitional and waiting places, social communication venues and connecting places. Taman Kambang Iwak ideally can meet the comfort needs of users. Comfort is a basic need that is felt physically and non-physically. Comfort is formed if humans try to condition the environment. The thermal conditions of Kambang Iwak Park affect the comfort of people who are active in their surroundings. The purpose of this study was to determine the level of thermal comfort in the Palembang Iwak Park. The research method used is a descriptive qualitative method and uses a Hobo Meter thermal measuring instrument accompanied by the calculation formula of the Thermal Comfort Index. The results showed that the level of thermal comfort in Taman Kambang Iwak Palembang was in the uncomfortable range. These findings should be taken into consideration for the Palembang City government to make improvements.